The Effects of A Bi-Weekly Yoga Program on Rheumatoid Arthritis (RA) Disease Activity: A Study on the Impact of a Bi-Weekly Yoga Program on Rheumatoid Arthritis patients (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In spite of significant breakthroughs in therapy, RA patients continue to struggle with gettingand staying in remission (RA). The positive effects of yoga on RA have been shown in preliminaryresearch. Yoga has been shown to provide a variety of health advantages, including reductions in painand improved mood, for those who are already receiving treatment for rheumatoid arthritis. Our researchwas to determine whether or not a twice-weekly yoga program improved disease activity, disability, orquality of life in rheumatoid arthritis patients compared to a control group. Patients were to be above theage of 18 and have been diagnosed with RA according to the American College of Rheumatology's (ACR)criteria. Data were summarized statistically and shown as meanSD or medianrange. Wilcoxon signedrankstest for paired data was used for analysis. Statistically substantial improvements in RA clinicalindicators and specifically HAQ scores were seen in our short pilot research of 12 yoga sessions for RA.There was a reduction or elimination of RA drug use in the yoga group. We speculate that more successmay be achieved with a longer course of therapy.